A Simple Solution for Estimating the Smear Effect Permeability Ratio Using Finite Element Method - Rufaizal Che Mamat; Azuin Ramli; Sri Atmaja P. Rosyidi (Journal of Rehabilitation in Civil Engineering)
The installation of a vertical drains system beneath the embankment results in enhanced soil consolidation in soft soil. This article explores the behaviour of soft soil stabilized with prefabricated vertical drains (PVDs) beneath embankments through finite element analysis. A multi-drain analysis, which varied the smear effect permeability ratio using both equivalent and plane strain models, was performed. Back-calculation of the permeability ratio of the smear effect is employed to adjust the model parameters. The analytical formulation employed the Cam-clay concept in combination with the smear effects. The study revealed that PVDs installation in the soft soil beneath the embankment increased the settlement rate and improved pore water pressure dissipation. Accurate prediction requires the estimation of the equivalent horizontal permeability using appropriate values of the smear effect permeability ratio. Incorporating the smear effect into the numerical analysis of vertical drains improved prediction accuracy. The article proposes a new approach for estimating the smear effect permeability ratio for soft soil stabilized with PVDs.